Hypercementosis: a rare finding in a patient with systemic lupus erythematosus - Shoor, Hitesh (BMJ Case Rep, 2014)
Hypercementosis is excessive deposition of non-neoplastic cementum over normal root cementum, which alters root morphology. This cementum may be either hypocellular or cellular in nature. The aetiopathogenesis of hypercementosis is ambiguous. Although most of the cases are idiopathic, several local and systemic factors are also linked to this condition, such as Paget's disease, acromegaly, vitamin A deficiency, etc. We report two rare cases of hypercementosis associated with systemic lupus erythematosus, not previously described in the literature, and also discuss the possible aetiopathogenesis.